2015
DOI: 10.1182/blood.v126.23.2117.2117
|View full text |Cite
|
Sign up to set email alerts
|

Glucose Levels Prior to Stem Cell Transplant Affect Length of Stay and 90-Day Readmission Rates

Abstract: Research Objectives: The Centers for Medicare and Medicaid Services (CMS) uses hospital readmissions as an indicator of quality of care during the index hospitalization. Patients with hematologic malignancies are at high risk of abnormal blood glucose levels, in particular hyperglycemia. Hyperglycemia during hematopoietic stem cell transplantation (HCT) is associated with adverse outcomes such as infection, delayed engraftment, and prolonged length of stay. Little is known about the association between pre-ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…First, there is growing evidence indicating that glucose imbalance in the body caused by hyperglycemia, diabetes mellitus, dyslipidemia, hypertension, or metabolic syndrome, alters normal cell function, leading to many musculoskeletal disorders and tissue damage, including osteoarthritis (OA). 9,27-36 Studies have reported association between health of the cartilage and glucose imbalance, independent of age, gender, and body mass index. 37-40 Although the relationships between hyperglycemia and its complications in the body are not fully understood, one of the widely studied evidence suggests hyperglycemia-induced overproduction of reactive oxygen species (ROS) by cells.…”
Section: Introductionmentioning
confidence: 99%
“…First, there is growing evidence indicating that glucose imbalance in the body caused by hyperglycemia, diabetes mellitus, dyslipidemia, hypertension, or metabolic syndrome, alters normal cell function, leading to many musculoskeletal disorders and tissue damage, including osteoarthritis (OA). 9,27-36 Studies have reported association between health of the cartilage and glucose imbalance, independent of age, gender, and body mass index. 37-40 Although the relationships between hyperglycemia and its complications in the body are not fully understood, one of the widely studied evidence suggests hyperglycemia-induced overproduction of reactive oxygen species (ROS) by cells.…”
Section: Introductionmentioning
confidence: 99%